(untitled) (Castilla. Estudios de Literatura, 2015)
The aim of this paper is to show insight into the Golden Age Spain a devotional work composed by the middle of the fifteenth century, the Imitatio Christi, which has been attributed to the Dutch Augustinian monk Thomas a Kempis. Being the most widespread work after the Bible in the Christian tradition, struck by the paucity of studies on diffusion and influence in Golden Age Spain. The present contribution, demonstrating that this work was widely disseminated Spain, by the large number of editions and translations, intended to open the field for future research in the literary field. We insist particularly in the case of Diego de Estella, whose work is postulated that the influence of the Imitatio Christi is so obvious that the model becomes transparent.